Challenges on the path to Treaty-based Local Government relationships - Bargh, Maria (Kōtuitui: New Zealand Journal of Social Sciences Online, 2021)
In this article I examine some of the challenges for Māori and Local Government on the path to Treaty-based Local Government relationships. I suggest significant challenges exist in three core areas. The first relates to the attitudes towards the ideas of Treaty-based Local Government and evident in common terminology which has a narrow focus on the identity of Māori as ‘representatives' rather than ‘Treaty partners’. The second area of challenge is in having Māori wards/constituencies established which, when they are established, are symbolically the beginnings of an acknowledgment of Treaty obligations and relationships. The third challenge is the lack of good data which limits understandings of Māori involvement in Local Government. In the second part of the article I ask whether any specific challenges can be seen that might impact on Treaty-based relationships in regard to Māori involvement as candidates and voters in Local Government elections.
Keywords: elections; local elections; local government; māori electorates; tiriti o waitangi/treaty of waitangi; treaty obligations; treaty-based relationships; voting